The Porter Hypothesis and Hyperbolic Discounting - Prabal Roy Chowdhury (Economics and Econometrics Research Institute (EERI), 2010)
We examine pollution-reducing R&D by a monopoly firm producing a dirty product. In a dynamic framework with hyperbolic discounting, we establish conditions under which the Porter hypothesis goes through, i.e. environmental regulation increases R&D, thus reducing pollution, as well as increasing firm profits. This is likely to hold whenever R&D costs are at an intermediate level, and the planning horizon of the firms is large.
Keywords: H2; L1; L2; L5; 330; Porter hypothesis; abatement tax; R&D; hyperbolic discounting